Effect of dietary restriction on sperm characteristic and oxidative status on testicular tissue in young rats exposed to long‐term heat stress. (23rd November 2014) - Aydilek, N.; Varisli, O.; Kocyigit, A.; Taskin, A.; Kaya, M. S.
Summary This study was conducted to evaluate the effects of dietary restriction on oxidative status and sperm parameters in rats exposed to long‐term heat stress. Forty healthy Sprague–Dawley rats, aged 2.5 month, were divided into four groups of 10 with respect to feeding and temperature regimen (room temperature (22 °C)‐ad libitum, room temperature–dietary restriction (40%), high temperature (38 °C)‐ad libitum, high temperature–dietary restriction). At the end of the 9th week, some oxidants (lipid hydroperoxide, total oxidant status, oxidative stress index) and antioxidants (total antioxidant status, sulfhydryl groups, ceruloplasmin, paraoxonase and arylesterase activities) were measured in the testis tissue. The concentration, motility, volume, abnormal sperm count, acrosome and membrane integrity of epididymal spermatozoon and intratesticular testosterone levels were evaluated. High temperature did not change oxidative and antioxidative parameters except for sulfhydryl groups and ceruloplasmin, yet it impaired all sperm values. Neither sperm values nor oxidative status apart from sulfhydryl groups, ceruloplasmin and arylesterase was affected by dietary restriction in the testis tissue. These results suggest that long‐term heat stress does not have a significant effect on testicular oxidative status, while the spermatozoa are sensitive to heat stress in young rats. Dietary restriction failed to improve the sperm quality and oxidative status except some individual antioxidant parameters; conversely, it decreased intratesticular testosterone level in the young rats exposed to long‐term heat stress.